Hubungan Situation Awareness dengan Kualitas Pengambilan Keputusan pada Situasi Man-Up Atlet Polo Air - Revanza Rizky Rahman; Adang Suherman; Kuston Sultoni (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
quality of decision-making in man-up situations among water polo athletes. The study employed an analytical observational design with a cross-sectional approach. A total of 52 water polo athletes participated in this study, selected using purposive sampling. Data on situational awareness were collected using the Situational Awareness Rating Questionnaire (SARQ), while the quality of decision-making was measured using the Scale of Effective Decision-Making in Sport (SEDMS). Data analysis was performed using correlation tests. The results showed that (1) Extrinsic Decision Making was positively and significantly associated with Indicative of the Demands of the Coach (r = 0.43; p < 0.01) and Indicative of Supply (r = 0.39; p < 0.01); (2) there was a significant positive relationship between Indicative of Supply and Indicative of Understanding (r = 0.51; p < 0.01); (3) there was a significant negative relationship between Intrinsic Decision Making and Indicative of Understanding (r = -0.49; p < 0.01); (4) aspects of situational awareness—particularly those related to the coach's demands and the availability of situational information—contribute to the quality of water polo athletes' decision-making in man-up situations. It is concluded that improving situational awareness can support effective decision-making in water polo. Keywords: Decision-Making Quality, Man-Up, Water Polo, Situational Awareness